Employee Payment Information System Petro Perkasa Indonesia - Ilham Pandu Anggoro; Husmul Beze; Suci Ramadhani (Politeknik Pertanian Negeri Samarinda, 2025)
In this modern and sophisticated era, technology has become a part of everyday life. Almost everything that is usually done manually, one example is the System. Payroll Information. Payroll Information System is a way to recap salaries and make reports on employee salary slips by using the internet as a medium. With the Payroll Information System website, it is hoped that it will make it easier for the company to recap employee salaries and make employee salary slip so that they can work effectively and efficiently in the process. In this study the author uses the prototype method using the PHP programming language with the Codeigniter3 framework. This employee payroll information system aims to assist in the admin process of managing employee payroll data and making it easier for employees to view and print salary data. The results of this employee payroll information system are 2 users, namely admin and employees.